Self-Esteem smong Undergraduate Students in a Nursing College in Kathmandu: A Descriptive Cross-sectional Study - Kansakar, Prajina; Acharya, Devaka Kumari (Journal of Institute of Medicine Nepal, 2024)
Introduction: Self-esteem is evaluation of self as being worthy and capable, the extent of which may be influenced by personal, interpersonal, and academic factors. Nursing is a stressful and demanding profession and requires positive self-esteem to develop confidence for healthy interaction with patients and health professionals. So, this study aimed to find out the self-esteem of undergraduate nursing students in a nursing college. Methods: A descriptive cross-sectional study was conducted among 118 undergraduate nursing students studying in first and third year of BSc Nursing and Bachelor of Nursing Science programs at Maharajgunj Nursing Campus, using proportional stratified simple random sampling. Data was collected through self-administered questionnaire with Likert Scale that measure self-esteem. Data analysis was done in SPSS version 16 using descriptive and inferential statistics. Results: Among 118 undergraduate nursing students, 63.6% (75) students had high self-esteem, 34.7% (41) had average self-esteem and 1.7% (2) had low self-esteem. Regarding the dimensions of self-esteem, mean percentages of the respondents were 78.7% (mean score 23.61 ± 3.59) for personal self-esteem, 80.1% (mean score 8.01 ± 1.48) for parentally derived self-esteem, 75.5% (mean score 26.44 ± 3.92) for academic self-esteem and 72.6% (mean score 18.15 ± 3.07) for social self-esteem. There was statistically significant association of self-esteem with age (p=0.001) and nursing education as their first professional choice (p=0.008). Conclusion: Majority of undergraduate nursing students have high level of self-esteem. More than one-third of them have average self-esteem. Self-esteem is low in academic and social dimension in comparison to personal and parental dimension. To strengthen students’ self-esteem teachers and campus administration, student support committee need to create supportive learning environment that would help to understand and deal with challenges in nursing education and practice, build self-confidence, self-worth, good communication. Parents’ support is necessary in building the students’ self-esteem.